'Everyone's magical and everyone's important': Karaoke community and identity in an American gay bar. Issue 2 (1st July 2016) - Kelley, Jamey
Although community music activities can take many forms, a 'participatory ethos' is central to most community music endeavours. Karaoke singing, the practice of public singing to an accompaniment track, which on the surface appears to emphasize solo performance, has the potential to provide a communal flow experience that could be described as community music within certain contexts. Karaoke singing has become a musical practice and form of entertainment around the world and in many types of settings. The case study used for this investigation is a karaoke culture at an LGBT establishment in a city on the American west coast. This study focuses on the formation of community as well as identity through karaoke performance. Additionally, the application of Turino's framework of participatory and presentational performance was used to examine how musical behaviours may encourage the formation of community and identity. Findings within this case study reveal the importance of the roles of the participants, the role of the facilitator, the agency of the individual, the fixity of musical forms, and musical texture to promote participatory experiences.